2023
DOI: 10.1101/2023.02.23.529704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glutamine metabolism inhibition has dual immunomodulatory and antibacterial activities againstMycobacterium tuberculosis

Abstract: As one of the most successful human pathogens, Mycobacterium tuberculosis (Mtb) has evolved a diverse array of determinants to subvert host immunity and alter host metabolic patterns. However, the mechanisms of pathogen interference with host metabolism remain poorly understood. Here we show that a novel glutamine metabolism antagonist, JHU083, inhibits Mtb proliferation in vitro and in vivo. JHU083-treated mice exhibit weight gain, improved survival, a 2.5 log lower lung bacillary burden at 35 days post-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Although our study focuses on lymphocytes, it is worth noting that glutaminolysis and the Warburg effect are found in various types of normal and malignant cells ( 34, 43 ). Moreover, the Warburg effect and the dependency on glutamines for cell proliferation are evolutionary conserved ( 4447 ). Therefore, it is reasonable to speculate that the principles discovered in this study are applicable to other cell types across species, particularly cells that produce large amount of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study focuses on lymphocytes, it is worth noting that glutaminolysis and the Warburg effect are found in various types of normal and malignant cells ( 34, 43 ). Moreover, the Warburg effect and the dependency on glutamines for cell proliferation are evolutionary conserved ( 4447 ). Therefore, it is reasonable to speculate that the principles discovered in this study are applicable to other cell types across species, particularly cells that produce large amount of energy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Glutaminolysis is one of the most important hallmarks of metabolic reprogramming. 4,5 Several studies, including those on various tumours and Mycobacterium tuberculosis infections, [6][7][8][9] have reported that the immunomodulatory effects of glutaminolysis are driven by their impact on T cells, and glutaminolysis mediates viral latency or reactivation and alters viral susceptibility to host cells. 10,11 However, the mechanisms by which metabolic-mediated CD4 + T cells influence virulence development are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%